2017
DOI: 10.1071/mf16005
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of juvenile bull sharks (Carcharhinus leucas) in the Navua River in Fiji

Abstract: Effective species conservation requires the protection of all stages of its life-cycle. The Shark Reef Marine Reserve (SRMR) in Fiji is a marine protected area where large numbers of adult bull sharks (Carcharhinus leucas) congregate due to food provisioning. At the end of a calendar year bull sharks leave the area for reproductive activity, but parturition sites are still unknown. Between February 2014 and January 2015, we interviewed local fishermen and conducted a fishing survey, so as to assess presence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…As exclusively juvenile sharks were encountered, it is likely that the studied nearshore environment constitutes another parturition ground in Fiji (Brown et al., ; Cardeñosa et al., ; Marie et al., ). Size ranges of C. limbatus and S. lewini (66 ± 4 and 52 ± 5 cm, respectively) were in accordance with size ranges of neonate and young‐of‐the‐year sharks from previously published studies (Castro, ; Castillo‐Géniz, Márquez‐Farias, Rodriguez de la Cruz, Cortés, & Cid del Prado, ; Brown et al., for S. lewini ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As exclusively juvenile sharks were encountered, it is likely that the studied nearshore environment constitutes another parturition ground in Fiji (Brown et al., ; Cardeñosa et al., ; Marie et al., ). Size ranges of C. limbatus and S. lewini (66 ± 4 and 52 ± 5 cm, respectively) were in accordance with size ranges of neonate and young‐of‐the‐year sharks from previously published studies (Castro, ; Castillo‐Géniz, Márquez‐Farias, Rodriguez de la Cruz, Cortés, & Cid del Prado, ; Brown et al., for S. lewini ).…”
Section: Discussionmentioning
confidence: 99%
“…While only two could be measured (76.1 cm, 78.2 cm), fishermen confirmed fairly regular catches of small sharks of different species within the river during informal discussions and interview sessions. Bull sharks are classified as “Near Threatened” (Simpfendorfer & Burgess, ) and despite having been documented in other river systems of Fiji (Cardeñosa et al., ), no scientific record had been made in the study area before.…”
Section: Discussionmentioning
confidence: 99%
“…The large majority of the species found in small fins (93.1%) inhabit coastal habitats (Yokota & Lessa, ; Carlson et al ., ; Yates et al ., ) and were either small species (62.9%), or large species captured as juveniles (at least 91.8% of the fins identified from large species). Many of the large species found in our small fin survey have been reported to use shallow coastal areas as juveniles, which frequently overlap with habitats used by small shark species (Simpfendorfer & Milward, ; Carlson & Brusher, ; Duncan & Holland, ; Yokota & Lessa, ; Yates et al ., ; Cardeñosa et al ., ). Therefore, it is possible that many of the small fins found in this preliminary survey are sourced from multi‐species fisheries in shallow, coastal habitats used by large species and also occupied by small species.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, sampling sites within the Rewa and Sigatoka Rivers (see below in the fishery‐independent surveys) were chosen following fishermen's local ecological knowledge (Rasalato et al, ) who suggested areas where they previously caught sharks and upon recommendations by the Ministry of Fisheries and Forests. The sampling scheme in the Navua River was similar to the one applied in Cardeñosa et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The latter study documented three juvenile bull sharks caught several kilometers upstream in the Ba River. Juvenile bull sharks were also confirmed in the Navua River close to the Shark Reef Marine Reserve (SRMR) where large adult bull sharks are abundant (Brunnschweiler, Abrantes, & Barnett, ; Cardeñosa, Glaus, & Brunnschweiler, ). In addition to these observed occurrences, results from an interview‐based survey documented small sharks in all of Fiji's major rivers (Rasalato, Maginnity, & Brunnschweiler, ) suggesting that in particular Fiji's largest riverine systems, the Rewa and Sigatoka Rivers on the southern coast of Viti Levu represent EFH for young bull sharks.…”
Section: Introductionmentioning
confidence: 99%